Aktivitas Antibakteri Ekstrak Dan Fraksi Daun Manggis (Garcinia Mangostana) Terhadap Staphylococcus aureus - Taufik Turahman; Ghani Nurfiana Fadma Sari (Jurnal Farmasi Indonesia, 2018)
Infectious diseases are still one of the important public health problems to be considered especially in developing countries. Mangosteen leaf (Garcinia mangostana L.) is a well-known plant that is useful as an antioxidant, antibacterial and anticancer. This study aims to determine the chemical content and antibacterial activity of ethanol extract, n-hexane fraction, ethyl acetate and water of mangosteen leaves (Garcinia mangostana L.) on Staphylococcus aureus by diffusion and dilution Mangosteen leaves were extracted by maceration using 96% ethanol then continued by fractionation using a liquid-liquid extraction method. Antibacterial activity was then tested using disc diffusion method with a concentration of 12.5%, 25% and 50%. Positive control used was ciprofloxacin 5μg / disk and negative control of 5% Tween 80. Dilution test was carried out on the most active extract by looking at the MIC and MBC. Identification of compound groups can be done using Thin Layer Chromatography method. The results of antibacterial activity testing showed that the diameter of the largest inhibitory zone in Staphylococcus aureus bacteria was found in the water fraction of mangosteen leaves at 50% concentration with inhibition zone diameter (10 mm). The results of the minimum MIC inhibitory level and the minimum suicide rate of MBC at a concentration of 12.5%. The TLC test results showed that in the extracts and fractions of mangosteen leaves contained flavonoids, saponins and steroids